If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 7) + (-5x + -14) = 0 Reorder the terms: (7 + 2x) + (-5x + -14) = 0 Remove parenthesis around (7 + 2x) 7 + 2x + (-5x + -14) = 0 Reorder the terms: 7 + 2x + (-14 + -5x) = 0 Remove parenthesis around (-14 + -5x) 7 + 2x + -14 + -5x = 0 Reorder the terms: 7 + -14 + 2x + -5x = 0 Combine like terms: 7 + -14 = -7 -7 + 2x + -5x = 0 Combine like terms: 2x + -5x = -3x -7 + -3x = 0 Solving -7 + -3x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -3x = 0 + 7 Combine like terms: -7 + 7 = 0 0 + -3x = 0 + 7 -3x = 0 + 7 Combine like terms: 0 + 7 = 7 -3x = 7 Divide each side by '-3'. x = -2.333333333 Simplifying x = -2.333333333
| (6x+8)+(-7x-19)= | | 4x+5=87-2x | | 14xy-21yz= | | 4x+3y=30 | | 2y-7=y+9 | | (x+4)(x-1)=24 | | 2(x+5)-6=16 | | -15=x+(-16) | | X-Y+A=3 | | X-Y+Z=3 | | x-2/12=5/6 | | -1+y/8=15 | | 4x+8y+20= | | 3x^3-7.5x^2-32=0 | | -3+m/9=10 | | -10=-2+1/2d | | 158-3x=24x+20 | | 6-7x=51-42x | | X-Y+C=3 | | 2x^2-1=9 | | 76-2x=10x-2x | | 12x-4=4x-3 | | 3y+4=7-4y | | 2(2x+7)+3(x+2)=5(x-1)-1 | | 6x-8=2x+32 | | 1+8x=22x+x | | 8y-2=7+6y | | (2x/3)=(4/7) | | 9x-1+8z-7x+z=0 | | 2x^2+17xy+8y^2= | | 8(2x+1)=11x+53+5x | | -x+9=x-21 |